Educational Philosophy and Teaching Style of Language and Literature (LL) Teachers (Journal of Natural Language and Linguistics, 2025)
This study examined the educational philosophies and teaching styles of Language and Literature (LL) teachers in Northern Samar, with the aim of describing the relationship between teachers’ philosophical orientations and their instructional practices. A descriptive–quantitative research design was employed, using a standardized survey conveniently responded by 20 LL teachers. The data were analyzed using frequency counts, percentages, and cross-tabulation. Results revealed that the respondents are mostly female, predominantly female, young to mid-career, moderately experienced, and academically well-prepared. Moreover, the majority of teachers adhered to Progressivism (55%), reflecting a learner-centered orientation that emphasizes inquiry, experiential learning, and democratic participation. Existentialism (20%) and Eclecticism (15%) followed, while Essentialism and Perennialism were minimally represented (5% each). In terms of teaching styles, the Delegator (40%) emerged as the most dominant, followed by teachers who employed a Combination of styles (25%), the Personal Model (20%), the Expert (10%), and the Authority (5%) approach. Cross-tabulation indicated a strong alignment between Progressivist philosophy and Delegator/Personal Model styles, while existentialist teachers balanced between Delegator and Expert orientations. Eclectic teachers demonstrated corresponding flexibility in their teaching styles. The findings suggest that LL teachers largely reflect global and national educational trends favoring student-centered and flexible pedagogies, while the limited presence of teacher-centered approaches signals a gradual decline of traditionalist models. It is recommended that professional development programs emphasize inquiry-based and collaborative learning strategies; curriculum implementation support eclectic practices to address diverse learners’ needs; DepEd and CHED sustain policies encouraging postgraduate studies to enhance teachers’ philosophical and pedagogical maturity; and further studies be conducted in the province and across different regions to validate and expand these findings.